Efektivitas Media Pembelajaran Papan Penjumlahan dalam Meningkatkan Kemampuan Operasi Penjumlahan pada Anak Berkesulitan Belajar - Dinda Laili Sarah Matondang; Martias Z (Dinasti Research, 2021)
The research objective was to improve the addition operation ability through the addition board learning media for children with learning difficulties in grade III SD N 11 Pauh Padang. This research uses a quantitative research approach with experimental method and single subject research (SSR) with A1 - B - A2 design. Design A1 - B - A2. At baseline conditions (A1) the child's ability to fluctuate ranges from 5% to 50%. The condition for intervention (B) ranged from 25% to 75%. At the baseline session (A2) it is already in a stable position, namely 100%. The results showed that the effect of the intervention using addition board media was effective in increasing the addition’s operation ability children’s with learning difficulties (X) class III at SD N 11 Pauh Padang.